Primary results of STRONG: An open-label, multicenter, phase 3b study of fixed-dose durvalumab monotherapy in previously treated patients with urinary tract carcinoma. (March 2022) - Sonpavde, Guru P.; Sternberg, Cora N.; Loriot, Yohann; Marabelle, Aurelien; Lee, Jae Lyun; Fléchon, Aude; Roubaud, Guilhem; Pouessel, Damien; Zagonel, Vittorina; Calabro, Fabio; Banna, Giuseppe L.; Shin, Sang Joon; et al.
Abstract: Background: Prior durvalumab (anti-PD-L1 agent) studies in platinum-refractory metastatic urothelial carcinoma evaluated a dose of 10 mg/kg administered every two weeks. The nonrandomised phase 3b STRONG study (NCT03084471) evaluated the safety and efficacy of fixed-dose durvalumab at a more convenient dosing schedule in a previously treated patient population, more similar to a real-world clinical setting. Patients and methods: 867 patients with urothelial or nonurothelial urinary tract carcinoma (UTC) who progressed on or after platinum or nonplatinum chemotherapy were treated with durvalumab 1500 mg every four weeks; 87% had an Eastern Cooperative Oncology Group performance status (ECOG PS) of 0–1, and 13% had an ECOG PS of 2. The primary end-point was the incidence of adverse events of special interest (AESIs), including immune-mediated AEs (imAEs). Secondary and exploratory end-points included overall survival (OS), objective response rate (ORR) and disease control rate (at six and 12 months) (DCR). Results: AESIs of any grade were reported in 51% of patients (8% grade ≥ 3). The incidence of imAEs was 11% (2% grade ≥ 3). The median OS was 7.0 months (95% confidence interval [CI]: 6.4–8.2) and ORR was 18% (95% CI: 14.8–20.6), with complete responses in 5% of patients and a DCR at six months of 19% (95% CI: 16.1–22.1). Conclusion: Fixed-dose durvalumab monotherapy every four weeks has an acceptable safety profile and yields durable clinical activity in previously chemotherapy-treated patients with UTC. Safety and efficacy are consistent with previous durvalumab studies and other anti-PD-1/PD-L1 agents in this setting. Clinicaltrials.gov identifier: NCT03084471 https://clinicaltrials.gov/ct2/show/NCT03084471 . Graphical abstract: Image 1 Highlights: STRONG, a phase 3b study, had a large population similar to a real-world setting. Patients had previously treated metastatic urothelial or nonurothelial carcinoma. Patients received a fixed dose of durvalumab 1500 mg intravenously every four weeks. The primary end-point was adverse events of special interest. Durvalumab had an acceptable safety profile and durable clinical activity.